The cellulose-degrading microbial community of the human gut varies according to the presence or absence of methanogens - Chassard, Christophe; Delmas, Eve; Robert, Céline; Bernalier-Donadille, Annick (FEMS microbiology ecology, 2010)
Cellulose-degrading microorganisms involved in the breakdown of plant cell wall material in the human gut remain rather unexplored despite their role in intestinal fermentation. Microcrystalline cellulose-degrading bacteria were previously identified in faeces of methane-excreting individuals, whereas these microorganisms were undetectable in faecal samples from non-methane excretors. This suggested that the structure and activity of the cellulose-degrading community differ in methane- and non-methane-excreting individuals. The purpose of this study was to characterize in depth this cellulose-degrading community in individuals of both CH4 statuses using both culture-dependent and molecular methods. A new real-time PCR analysis was developed to enumerate microcrystalline cellulose-degrading ruminococci and used to confirm the predominance of these hydrolytic ruminococci in methane excretors. Culture-dependent methods using cell wall spinach (CWS) residue revealed the presence of CWS-degrading microorganisms in all individuals. Characterization of CWS-degrading isolates further showed that the main cellulose-degrading bacteria belong essentially to Bacteroidetes in non-methane-excreting subjects, while they are predominantly represented by Firmicutes in methane-excreting individuals. This taxonomic diversity was associated with functional diversity: the ability to degrade different types of cellulose and to produce H2 from fermentation differed depending on the species. The structure of the cellulolytic community was shown to vary depending on the presence of methanogens in the human gut.